Practical approaches to methods validation and essential instrument - Chan, Chung Chow; Lam, Herman; Xue, Ming Zhang (Hoboken, New Jersey : John Wiley, 2010)
"The objective of this book is provide information in same practical, hands-on manner as the first book "Analytical Method Validation and Instrument Performance Verification", on important, but more advance topics. It will focus on additional and supplemental methods, instruments, and electronic systems that are used in pharmaceutical, biopharmaceutical, and clinical testings. These tests will generate reliable data that is in compliance with current Good Manufacturing Practices (cGMP) and will follow Good Analytical Practices"
Complement to: Method validation and instrument performance verification / edited by Chung Chow Chan ... [et al.]. c2004
Includes bibliographical references and index
Keywords: Drugs -- Analysis -- Methodology -- Evaluation; Laboratories -- Equipment and supplies -- Evaluation; Laboratories -- Instruments -- Evaluation; Chemistry, Pharmaceutical -- instrumentation; Chemistry, Pharmaceutical -- methods; Clinical Laboratory Techniques -- standards; Technology, Pharmaceutical -- methods